2021
DOI: 10.3389/fncel.2021.660812
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Hereditary Hearing Loss: Pathology of the Inner Ear

Abstract: Inherited forms of deafness account for a sizable portion of hearing loss among children and adult populations. Many patients with sensorineural deficits have pathological manifestations in the peripheral auditory system, the inner ear. Within the hearing organ, the cochlea, most of the genetic forms of hearing loss involve defects in sensory detection and to some extent, signaling to the brain via the auditory cranial nerve. This review focuses on peripheral forms of hereditary hearing loss and how these impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Like hearing loss ( 49 , 88 ), vestibular disorders may have multiple causes, including genetics, aging, drugs, immune and environmental factors (e.g., infections, noise exposure) ( 89 ). The prevalence of vestibular impairment is high in children and adults with sensorineural hearing loss (SNHL), between 20 and 70% ( 90 , 91 ).…”
Section: Vestibular Disorders Associated With Hearing Loss: Diversity...mentioning
confidence: 99%
See 1 more Smart Citation
“…Like hearing loss ( 49 , 88 ), vestibular disorders may have multiple causes, including genetics, aging, drugs, immune and environmental factors (e.g., infections, noise exposure) ( 89 ). The prevalence of vestibular impairment is high in children and adults with sensorineural hearing loss (SNHL), between 20 and 70% ( 90 , 91 ).…”
Section: Vestibular Disorders Associated With Hearing Loss: Diversity...mentioning
confidence: 99%
“…As a result, the available mutant mice, most of which also display vestibular deficits ( Table 1 ; Supplementary Table S1 ), have provided valuable information about the key pathways leading to vestibular dysfunction. In studies of organ patterning or MET, the use of more distantly related animal models, such as zebrafish, Drosophila , or C. elegans , has facilitated the identification of key conserved core biological features and highlighted species-specific features ( 88 , 153 157 ).…”
Section: Detailed Mechanisms Of Vestibular Function: Insight From Ani...mentioning
confidence: 99%
“…Signal Transmission by Auditory and Vestibular Hair Cells DOI: http://dx.doi.org/10.5772/intechopen.107944 damage, genetic mutation or ageing. More and more gene mutations are becoming identified that produce, or cause predisposition to, inner ear disorders due to hair cell malfunction or even death [30,31]. At the end of this chapter, we look at the different strategies that are being developed as potential therapies to regenerate hair cells or to restore their function.…”
Section: ) Right: In the Vestibular Epithelia Afferent Nerve Terminal...mentioning
confidence: 99%
“…The SV plays an important role in HHL pathogenesis. Several researchers have previously summarized the histopathologic findings associated with these genetic mutations, and atrophy or fibrosis of the SV has been observed in many cases, often caused by mutations in GJB2, COCH, and MYH9, as well as by Usher syndrome, and Alport syndrome (Bommakanti et al, 2019;Nicolson, 2021). Syndromic and non-syndromic hereditary hearing loss are the two main forms of hereditary hearing loss (HHL) (Egilmez and Kalcioglu, 2016).…”
Section: Hereditary Hearing Lossmentioning
confidence: 99%